Analisis Kebijakan Dividen terhadap Nilai Perusahaan yang Terdaftar dalam Index LQ-45 - Sulpadli Sulpadli; Firman Wahyudi; Sigit Dwi Prakoso; Darmono Darmono; Muhammad Bayu; Djupiansyah Ganie; Siti Munawaroh; Caetano Carceres Correia (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
The purpose of the research was to find out and analyze whether there was an influence of dividend policy on the value of companies listed in the LQ-45 index. Based on the results of the study, it can be seen that there is a positive and significant influence between dividend policies on company value. The dividend policy variable has a tcal value of 4,284 and a ttable value of 2,160. This shows that the tcount is larger than the table so that HO is rejected and Ha is accepted, meaning that the dividend policy has an effect and is significant on the value of companies listed in the LQ-45 index. This the hypothesis put forward is acceptable.